Pneumopericardium causing pericardial tamponade - Ryan J. Fink (Clinical Case Reports, 2020)
Abstract Pneumopericardium can be severe enough to cause pericardial tamponade physiology. These patients can be hemodynamically unstable and require pericardial drainage.